The Effects of Ethical Leadership and Abusive Supervision on Job Search Behaviors in the Turnover Process - Palanski, Michael (Journal of business ethics, 2014)
Drawing upon the unfolding model of turnover and the dual-process theory of information processing, we examined the roles which ethical leadership and abusive supervision play in the turnover process. The central conclusion of this study is that ethical leadership influences job satisfaction, which then influences intentions to quit, which then impacts job search behaviors. Conversely, abusive supervision, which is the conceptual opposite of ethical leadership, has a negative influence on job satisfaction with corresponding impacts on intentions to quit and job search behavior. But, unlike ethical leadership, which does not directly lead to job search behavior, abusive supervision can also directly make people so upset that they initiate job search behaviors. Moreover, findings indicate that even low levels of abusive supervision can neutralize high levels of ethical leadership. Implications for research and practice in human resource management are discussed.